(untitled) (Journal of Surgical Sciences, 2019)
Cavernous hemangioma of colon and rectum is a rare disease, with no more than 200 cases reported in the literature so far. The rectosigmoid is the most common site of this disease in the gastrointestinal tract. We report a case of a 32-year-old male with recurrent episodes of per-rectal bleeding, who was finally diagnosed of cavernous hemangioma of sigmoid colon and ano-rectum. The lesion, 23 cm in length, occupied the whole circumference of the sigmoid colon and rectum extending up to the margin of the anal sphincter. Ultra-low anterior resection with hand-sewn colo-anal anastomosis and temporary loop ileostomy was carried out. The patient is in regular follow up. He is now symptom free. Journal of Surgical Sciences (2014) Vol. 18 (2) : 83-86